The neurophysiology and assessment of sports-related head injuries - Lovell, M. (Physical Medicine & Rehabilitation Clinics of North America, 2009)
This article provides a review of contemporary standards for the management of athletes who have sustained a sports-related head injury. Recent research regarding concussion management is reviewed with specific reference to clinical care. The use of neuropsychologic testing in sports also is reviewed, and a systematic protocol for the management of sports-related concussion is presented.